Crystallization of SiO2-CaO-Na2O Glass Using Sugarcane Bagasse Ash as Silica Source - Teixeira, Silvio Rainho [UNESP]; Romero, Maximina; Rincon, Jesus Ma. (Wiley-Blackwell, 2010)
This work reports the feasibility results of recycling sugar cane bagasse ash (SCBA) to produce glass-ceramic. The major component of this solid residue is SiO2 (>89%). A 100 g batch composition containing ash, CaO and Na2O was melted and afterward, poured into water to produce a glass frit. The crystallization kinetic study by nonisothermal method was performed on powder samples (<63 mu m) at five different heating rates. Wollastonite is the major phase in crystallization at T>970 degrees C, and below this temperature there is a predominance of rankinite. The crystallization activation energies calculated by the Kissinger and Ligero methods are equivalent: 374 +/- 10 and 378 +/- 13 kJ/mol. The growth morphology parameters have equal values n = m = 1.5 indicating that bulk nucleation is the dominant mechanism in this crystallization process, where there is a three-dimensional growth of crystals with polyhedron-like morphology controlled by diffusion from a constant number of nuclei. However, differential thermal analysis (DTA) curves on both monolithic and powder glass samples suggest that crystallization of the powder glass sample occurs through a surface mechanism. The divergence in both results suggests that the early stage of surface crystallization occurs through a three-dimensional growth of crystals, which will then transform to one-dimensional growth.